Sanksi Pidana Pelaku Tindak Pidana Order Fiktif dalam Transportasi Berbasis Aplikasi Online Prespektif Hukum Positif dan Hukum Pidana Islam: Criminal Sanctions for Perpetrators of Fictitious Order Crimes in Online Application-Based Transportation from the Perspective of Positive Law and Islamic Criminal Law - Wasil Wasil (CLEAR: Criminal Law Review, 2023)
The focus of the problem examined in this thesis is 1) Is the application of criminal sanctions against perpetrators of fictitious criminal acts in online application-based transportation in accordance with the criminal sanctions system in Indonesia? 2) How does Islamic criminal law review the criminal sanctions for criminal acts of fictitious orders in online application-based transportation? Researchers use normative juridical research or library research using several approaches, namely the statutory approach, the case approach and the conceptual approach. The researcher reached the conclusion 1) Based on the Indonesian criminal system, the judge in handing down the sentence was in accordance with the Indonesian criminal system. As in Article 51 jo 35 paragraph (1) Law no. 19 of 2016. As a form of criminal act of online fraud through fictitious orders. 2) Fictitious orders are fake orders, using fake accounts to deceive the company. Fictional orders are included in the category of jarimah ta'zir, because at the time of the Prophet Muhammad SAW, technology in the form of the internet, computers or cellphones had not been discovered as a tool for committing crimes. So there is not a single verse that explains this fictitious order case. In Islamic criminal law, a fictitious order can be considered an act of fraud. So the sanctions are not qisash and had but rather punishments including Jarimah in ta'zir, then the punishment or sanctions for perpetrators of fictitious orders are determined by the Judge or Ulil Amri (government). Fokus masalah yang diteliti dalam penelitian ini adalah 1) Apakah penerapan sanksi pidana terhadap pelaku tindak pidana order fiktif dalam transportasi berbasis aplikasi online telah sesuai dengan stelsel pemidanaan di Indonensia? 2) Bagaimana tinjauan hukum pidana Islam terhadap sanksi pidana tindak pidana order fiktif dalam transportasi berbasis aplikasi online? Peneliti menggunakan jenis penelitian yuridis normatif atau penelitian kepustakaan (library research) dengan menggunakan beberapa pendekatan, yakni pendekatan peraturan perundang-undangan (Statutte Approach), pendekatan kasus (Case Approach), dan pendekatan konseptual (Conceptual Approach). Peneliti memperoleh kesimpulan 1) Berdasarkan stelsel pemidanaan Indonesia, hakim dalam menjatuhkan pemidanaan sudah sesuai dengan stelsel pemidanaan Indonesia. Sebagaimana dalam Pasal 51 jo 35 ayat (1) Undang-Undang No. 19 Tahun 2016. Sebagai bentuk tindak pidana penipuan online melalui order fiktif. 2) Order fiktif merupakan orderan paslu, dengan menggunakan akun palsu untuk menipu perusahaan. Order fiktif masuk dalam katagori jarimah ta’zir, karena pada zaman Nabi Muhammad SAW belum ditemukan teknologi berupa internet dan komputer maupun ponsel sebagai alat dalam melakukan kejahatan. Sehingga tidak ada satu pun ayat yang menjelaskan mengenai kasus order fiktif ini. Di dalam hukum pidana Islam, order fiktif dapat dikatakan perbuatan penipuan. Sehingga sanksinya bukanlah qisash dan had melainkan hukuman termasuk Jarimah dalam ta’zir, maka hukuman atau sanksi bagi pelaku order fiktif ditentukan oleh Hakim atau Ulil Amri (pemerintah).